Bicuspid aortic valve with dissecting aortic aneurysm in an African - Ogbemudia, E.J.; Ogbomo, A. (SA Heart Journal, 2020)
Bicuspid aortic valve (BAV) is a relatively rare congenital heart disease (CHD) in Africans compared to caucasians and it is an independent risk factor for aortic aneurysm and dissection. We therefore report a case of a 51-year old farmer who presented with clinical features of heart failure (HF). He had a diastolic murmur loudest in the aortic area. Echocardiography revealed BAV with regurgitation. The aortic root and ascending aorta were dilated with dissection flaps which mimicked a double aortic valve. Computed Tomography angiography of the aorta confirmed Debakey’s type 1 (Stanford A) dissecting aortic aneurysm (DAA). He was managed for HF due to chronic aortic regurgitation and referred for surgery. BAV is a relatively rare CHD in Africans and is a strong risk factor for DAA. Long-term monitoring of the aorta and timely surgical intervention are recommended when indicated.